Некаталическое термическое обезвреживание вентиляционных выбрасов, содержащих органику, в волне фильтрационного горения - Протопопов, Р. Я.; Себко, Вадим Вадимович; Шапорев, Валерий Павлович (НТУ "ХПИ", 2012)
Проведено экспериментальное и расчетное исследование процесса термического обезвреживания вентиляционных выбросов в волне фильтрационного горения метана. Представлена модель процесса.

An experimental and numerical research of thermal decontamination process of ventilation emissions in the wave of filtration combustion of methane. The model of the process presented.
Non-catalytic thermal decontamination in high-voltage spark discharge of ventilating pollutions containing organic chemistry
Keywords: эксперимент; исследование; метан; модель; high-voltage discharge; nichrom electrodes; thermal decontamination; research